Шаліли, шаліємо, чи будемо шаліти далі? (До питання новацій у сучасному художньому текстилі) - Печенюк, Т. (Студії мистецтвознавчі, 2009)
The article is dedicated to the problems of decorative textile modern innovative art in Ukraine. The discourse basis is the practice of establishing and development of Lviv biennale “Textile excitement” which are classified, according to the author, as an experimental and visual platform of Ukrainian contemporary textile art. In order to determine the subject of the present experiment in textile creation it has been suggested to consider the notions of “innovation-experiment” in generally artistic interpretation basing on the context of modern European textile biennale and other separate art projects.